An Overview of Malaysia’s Retail Organic Foods Market and Its Consumption Behavior - Hussin, Harniyati; Abdul Wahid, Nabsiah (Advances in Social Sciences Research Journal, 2024)
Growing global awareness of health and environmental sustainability has significantly increased the demand for organic foods, a trend gaining traction in Malaysia. This research provides a comprehensive overview of consumer consumption patterns and purchase intentions for organic foods in Malaysia’s retail sector, identifying key factors influencing their choices. The study examines Malaysia’s broader food retail landscape, focusing on the growing organic segment and its evolving consumption patterns. It also explores the organic food market, considering domestic production and the availability of imported goods that shape consumer choices and market growth. The study offers practical insights into consumer decision-making within the retail food market by examining consumption behavior, such as purchase intentions. The review uncovers critical insights into the organic food market, including its size, rising demand and consumption trends, government and retailer initiatives, and the demographic profiles of consumers who purchase or intend to purchase organic foods. These findings contribute to existing research on organic food consumption in Malaysia and provide valuable guidance for policymakers, government agencies, and retailers aiming to enhance the adoption of organic foods in the Malaysian retail sector.